Laser nonlinearity compensation model using taylor series expansion for free space optical communication system - Maiteeg, A. B. (2007)
Free-space optical communication (FSO) is an optical communication technology that uses light propagating in free space to wirelessly transmit data for telecommunications or computer networking.